2020
DOI: 10.1093/neuonc/noaa091
|View full text |Cite
|
Sign up to set email alerts
|

Modeling glioblastoma invasion using human brain organoids and single-cell transcriptomics

Abstract: Background Glioblastoma (GBM) consists of devastating neoplasms with high invasive capacity, which have been difficult to study in vitro in a human-derived model system. Therapeutic progress is also limited by cellular heterogeneity within and between tumors, among other factors such as therapy resistance. To address these challenges, we present an experimental model using human cerebral organoids as a scaffold for patient-derived GBM cell invasion. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 47 publications
2
92
1
Order By: Relevance
“…The authors showed that GSCs were able to invade and proliferate within the healthy brain organoid and to form interconnecting microtubes. Another study confirmed that GSCs transcriptionally adapted to mini-brain microenvironment in line with their in vivo behavior (87). Although Linkous et al showed similar invasion of GSCs in cerebral organoids of different age, others reported GBM cell invasion only in early stage cerebral organoids, whereas invasion into fully mature organoids was halted (88).…”
Section: Gbm Invasionmentioning
confidence: 75%
See 1 more Smart Citation
“…The authors showed that GSCs were able to invade and proliferate within the healthy brain organoid and to form interconnecting microtubes. Another study confirmed that GSCs transcriptionally adapted to mini-brain microenvironment in line with their in vivo behavior (87). Although Linkous et al showed similar invasion of GSCs in cerebral organoids of different age, others reported GBM cell invasion only in early stage cerebral organoids, whereas invasion into fully mature organoids was halted (88).…”
Section: Gbm Invasionmentioning
confidence: 75%
“…Similar cocultures of human cerebral organoids could be applied to patientderived GBM organoids in the future. Of note, the protocol is tedious, as efficient GBM invasion inside the cerebral organoid often requires removal of the ECM embedding (87,88). If ECM is preserved, GBM cells primarily adhere to the matrix and grow on top of the surface.…”
Section: Gbm Invasionmentioning
confidence: 99%
“… 2019 ; Krieger et al . 2020 ). Such cancer-bearing organoids promise personalized medicine by exploring most effective therapeutics for a given patient as well as the development of novel therapeutics (Plummer et al .…”
Section: Translational Aspects Of Mps: Modelling Neuropathiesmentioning
confidence: 99%
“…The second relies on the introduction of patient derived GSCs into organoids, which is particularly well suited for understanding clinical characteristics following initial tumor formation. Due to the central role of GSCs as the cell type that drives tumor progression and recurrence [33], these efforts have focused on introducing GSCs into COs, either as single cells [34][35][36][37] or as GSC spheres [38]. Characteristic results of the latter method, which is utilized in our laboratory, are presented in Fig.…”
Section: Cerebral Organoids As An Emerging Model Systemmentioning
confidence: 99%
“…Given the differences in human and mouse brain structures [40], this co-culture system was not further used aside from being a proof-of-principle for future improvements. Subsequently, several other groups utilized the fusion approach as an ex vivo model of GBM [32,[34][35][36][37] and drug screening [31,36].…”
Section: Co-culturing Systems Of Gbm and Cerebral Organoidsmentioning
confidence: 99%